PAUS FRANSISKUS: TELADAN KEPEMIMPINAN GEREJAWI DI ABAD KE-21 - Andersius Namsi (Jurnal Arrabona, 2019)
In the 21st century it appears that leadership in both the secular and religious world has declined. But in the decline of leadership, we can see and emulate a religious leader as well as a religious leader who set an example of leadership even within the scope of the Church in the 21st century.